The Effectiveness of Transcutaneous Electrical Nerve Stimulations Oral Exercise in Hypo Salivation Among Type II Diabetic Patients Over Submandibular Glands: Life Sciences-Physiotherapy - Kirupa, K.; Divyamary, S.M.; Nisha, R. Nithya; Saraswath, K; Kaviya, D.P.; Aishwarya, B.; Lakshmi, N. Nimisha; Swetha, K. (International Journal of Life Science and Pharma Research, 2023)
This study was conducted to improve the patient’s oral function, especially dry mouth (xerostomia) and infection. The aim of this study is to analyse the effectiveness of transcutaneous electrical nerve stimulation vs. oral exercise in reducing hypo salivation among type II diabetic patients over the submandibular glands. The secretion of saliva is critical for oral health, digestion, prevention of infections, and the healing process. Hypo salivation is defined as a decrease in saliva in the mouth. It is the most common type II diabetic problem among adults and older people. It is estimated to occur in 10 of every 35 adults. Because of hypo salivation, Type II diabetic adults may experience infection, cavities, soreness, ulcers, a decrease in taste sensation, and difficulty in water balance. Hypo salivation leads to many complications that make the condition of the diabetic patient even worse. Hence, there is a wide need for treatment techniques to be searched for, and they must be applicable to all communities. There are various therapies to improve the salivary rate, but there is a need to analyse the technique that gives better outcomes with a short intervention with easy accessibility. The materials and method of this study follow a simple method and are evidenced with a noninvasive diagnostic tool. Saliometry by the low-spitting method was used to measure the salivary flow rate. The methodology was a comparative study design with a pre-post-test. Samples were selected from 40 volunteers based on inclusion criteria. Group A: Transcutaneous Electrical Nerve Stimulation, 8 sessions, 20 minutes each, twice a week for 4 weeks. Group B: Oral exercise, 16 sessions, 2 minutes each, in 3 sets for 4 weeks. At the end of 30 days of sessions, the salivary flow rate has increased from 0.36 to 1.03 ml/min and the SD from 0.12 to 0.91 for Group A, and from 0.34 to 0.56 ml/min and the SD from 0.2 to 0.4. The result concludes that both groups showed improvement, while group A, which received transcutaneous electrical nerve stimulation, was comparatively better than group B, which received oral exercise